Model Pembelajaran Transformatif Berbasis Learning How To Learn Untuk Peningkatan Kreativitas Belajar Mahasiswa - .., Hardika (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
The purpose of this research is to solve the problem of learning related to theÂ effort to improve creativity in learning for students university. InnovationÂ of learning that developed is a transformative model of learning based onprincip of learning â€œhow to learnâ€. Research method that used is researchÂ and development (RD). The result of this research is transformativeÂ learning based on learning â€œhow to learnâ€ able to create flxibility ofÂ students to actuate and to express within learning activities so that it ableto create creativity of learning.Keywords: Transformative learning, learning how to learn, performanceÂ of learning.